Enhancing Rice Productivity in West Africa through Genetic Improvement - Saito, Kazuki; Sokei, Y.; Wopereis, Marco C.S. (Wiley, 2012)
Rice yields have stagnated in West Africa at 1 to 2 Mg ha−1 because of unfavorable rice environments and poor management practices. Interspecific rice cultivars, the New Rice for Africa (NERICA), were developed by crossing Asian rice (Oryza sativa L.) and African rice (O. glaberrima Steud.) to improve upland and lowland rice productivity in resource-poor farmers’ fields. This paper provides an overview of recent studies, performed by the Africa Rice Center and its partners, on evaluation of growth and yield performance of upland and lowland NERICA cultivars and modern Asian rice cultivars including the improved upland indica cultivars often termed aerobic rice. Upland NERICA cultivars were found to lack the expected combination of superior yield potential with weed suppressive ability (WSA) and adaptation to low soil fertility, instead sharing similarity in these characteristics with their O. sativa parent WAB56-104 but remaining inferior to their O. glaberrima parent CG 14 in terms of tillering ability and WSA. Some aerobic rice cultivars were identified for high yielding ability, strong WSA, and superior adaptation to low-fertility uplands and water-limited lowlands. Some lowland NERICA cultivars outyielded improved lowland O. sativa checks and aerobic rice cultivars in favorable lowlands, whereas they did not perform well in water-limited lowlands. The implications of these findings for future challenges for genetic improvement in West Africa are discussed.